Advancing Teaching Mathematics in Students at Universities of Economics for Sustainable Development - N. A. Burmistrova (Научный диалог)
The article is devoted to the advanced nature of education for sustainable development. The research urgency is caused by necessity of formation of strategy of education for sustainable development in Russian higher education. A review of the most important international documents is made (Strategy of European Economic Commission of the UN of education for sustainable development, Global action programme on ESD, Incheon Declaration of “Education-2030,” Program of sustainable development for the period till 2030, etc.), allowing to concretize the principles of education for sustainable development. Special attention is paid to the principle of advancing training in terms of organization of training in mathematics at the University of Economics. As a means of implementing the principle of advancing teaching of mathematics it is proposed to use the method of mathematical modelling as a promising direction of research and problem solving in the economic sphere of activities in favour of sustainable development. The author noted the importance of the ability to build and use mathematical models to describe and predict real processes, which in turn, demonstrates the possibility of forming a transformative intelligence as readiness for integrated use of intuition, logical thinking and quantitative assessments to develop the skills of creative solutions to life and professional problems in the conditions of variability and uncertainty.